Urgensi Kepemimpinan Demokratis dalam Membangun Integritas di Lingkungan Madrasah - Eka Mardiani (The Magister of Islamic Education Study Program of Postgraduate IAIN Pontianak, 2022)
This study aims to provide information regarding the importance of democratic leadership in building integrity in Madrasah Tsanawiyah which is an Islamic education Institution. The type of research used is library research, with the following results (1) The leader is the main mover of the organization, and the authority of the organization is in the hands of the leader. Leaders are also the key to the success of an organization. Likewise, Organizational failure also depends on how the leaders carry out the leadership process. (2) the provision of excellent service to the Islamic education environment can be carried out optimally if the leadership system is managed democratically under the control of the leader as needed, (3) With democratic leadership, it is hoped that the values of integrity will be more easily realized, to create conditions in which educational institutions Islam continues to exist to provide quality work so that it is useful for all aspects of the life of the nation and state. Based on the three findings above, it can be concluded that democratic leadership is an undeniable important part of building integrity in Islamic educational institutions, especially at madrasah tsanawiyah. ABSTRAKPenelitian ini bertujuan untuk memberikan informasi terkait pentingnya kepemimpinan demokratis dalam membangun integritas di madrasah Tsanawiyah yang merupakan lembaga pendidikan Islam. Jenis penelitian yang digunakan ialah library research, dengan hasil sebagai berikut: (1) Pemimpin merupakan penggerak utama organisasi, otoritas organisasi berada di tangan pemimpin. Pemimpin juga menjadi kunci keberhasilan dari suatu organisasi. Begitu juga kegagalan organisasi juga tergantung bagaimana pemimpin melakukan proses kepemimpinanya. (2) Pemberian layanan prima kepada lingkungan pendidikan Islam dapat dilakukan secara optimal jika sistem kepemimpinan dikelola secara demokratis atas kendali pemimpin sesuai kebutuhan, (3) Dengan adanya kepemimpinan demokratis, diharapkan nilai-nilai integritas akan lebih mudah terwujud, guna menciptakan kondisi dimana lembaga pedidikan islam terus eksistensi memberikan sebuah karya yang berkualtias sehingga berguna bagi seleruh aspek kehidupan berbangsa dan bernegara. Berdasarkan tiga temuan di atas maka dapat disimpulkan, kepemimpinan demokratis menjadi bagian penting tak terbantahkan dalam rangka membangun integritas di lembaga pendidikan Islam terutama pada Madrasah Tsanawiyah. Kata kunci: Kepemimpinan Demokratis, Membangun Integritas